DEVELOPMENT OF RECOMMENDATIONS ON THE CHOICE OF TYPES OF ROAD MAPS IN THE RECONSTRUCTION OF VICTIMS OF UKRAINIAN SETTLEMENTS - Divizinyuk, М.; Soshinskiy, O.; Shevchenko, O.; Shevchenko, R. (Municipal economy of cities. Series: «Economy science», 2022)
The scientific task of developing recommendations for the selection of types of road maps as an element of engineering structures with the predictive effect of minimizing fragmentation of civilians in case of fire damage by high-explosive munitions during reconstruction of affected settlements of Ukraine. The analysis of literature sources proved the need for detailed research of engineering and building materials and structures in order to increase their resistance to the fire effects of modern ammunition used in Russian aggression against the people and territory of Ukraine. It has been proven that the use of explosive weapons in populated areas leads to numerous casualties and injuries to civilians. The detonation of high-explosive munitions is enhanced in enclosed or semi-enclosed spaces, such as buildings, tunnels, narrow streets or vehicles. This leads to a higher proportion of deaths due to secondary damage. It is established that the recommendations on the choice of types of road maps as an element of engineering structures with a predictive effect of minimizing fragmentation of civilians in case of fire damage by high-explosive munitions, allow to further develop a methodology for developing road surfaces damage to the civilian population by 30% of the primary and 70% of the secondary factors of fire damage by high-explosive fragmentation munitions. From so against fragmentation of the road surface and competent engineering placement and layout of buildings in the settlement and type in can significantly increase the likelihood of human survival in cities and villages. Future engineering solutions should also take into account regional differences in structures and building materials. Further research should be conducted to determine the minimization effects of fire damage from the use of building materials with regional characteristics. As a result, the use of explosive weapons in populated areas leads to numerous victims and injuries of the civilian population. In addition to the human cost, fire damage to populated areas results in significant damage to basic infrastructure, homes and businesses. At the same time, the detonation effect of high-explosive munitions is enhanced in closed or semi-closed spaces, such as buildings, tunnels, narrow streets or vehicles. This leads to a higher proportion of deaths due to secondary damage. Since then, there is a need to develop engineering and technical recommendations, which, based on the quantitative assessment of the effects of fire damage, would allow to form measures against potential factors of secondary damage during the reconstruction of cities and villages. of Ukraine. The developed recommendations on the selection of types of road maps as an element of engineering structures with the predictive effect of minimizing shrapnel damage to the civilian population in the event of fire damage by high-explosive munitions allow to further develop a methodology for the development of road surfaces in cities and towns of Ukraine during their reconstruction. This will reduce the probability of damage to the civilian population by 30% from primary and by 70% from secondary factors of fire damage by high-explosive munitions.